Influencia de la inteligencia emocional en la gestión directiva de los directores de educación primaria de menores de las instituciones educativas públicas del distrito de Iquitos 2022 - Vásquez Matute, Sol Patricia (2024)
The main objective of this study was to determine the influence of emotional intelligence in the management of public elementary schools in the district of Iquitos 2022. The research project is quantitative with a correlational design and non-experimental degree of explanation. It consisted of 21 elementary school principals and the sample consisted of 191 teachers, chosen by the stratified sampling method by proportional allocation. The survey technique was applied and the instruments used were Bar-On's ICE (Emotional Quotient Inventory) test for emotional intelligence and the questionnaire of questions for managerial management. The most relevant findings were the following: The management style of elementary school principals in the district of Iquitos 2022 is significantly influenced by emotional intelligence. When applying the Chi square statistical test, significant findings were found, allowing us to accept the hypothesis of the study.